The Effect of Two Different Types of Probiotics on the Physical and Chemical Properties of Rice Straw - Risqi Dava Saputra; Catur Suci Purwati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Rice straw is one alternative feed resource that has potential for use as livestock feed under certain conditions. This potential is indicated by its abundant availability, while a large proportion remains underutilized. Unfortunately, disposal is often carried out by burning in agricultural fields, which leads to air pollution. This study was conducted to evaluate the fermentation of rice straw using different fermentors, namely MA-11 mixed with molasses and Starbio, and their effects on the physical and chemical properties of rice straw. The experiment employed a Completely Randomized Design (CRD) with three treatments and four replications: P0 (fermentation without probiotics), P1 (fermentation with 3% MA-11 mixed with molasses), and P2 (fermentation with 3% Starbio). The observed variables included physical characteristics (color, aroma, and texture) and chemical composition (dry matter and pH). The findings indicated that fermenting with MA-11 combined with molasses and Starbio enhanced both the physical and chemical attributes of rice straw silage. In terms of physical characteristics, the fermented samples displayed a yellowish-brown hue, a mildly acidic scent, and a somewhat rough texture. From a chemical perspective, the dry matter percentage rose from 91.97% (P0) to 92.37% (P1) and 92.37% (P2), although this change was not statistically significant (P>0.05). At the same time, pH levels showed a notable decrease from 6.25 (P0) to 5.50 (P1) and 5.75 (P2). Thus, it can be concluded that the fermentation of rice straw utilizing MA-11 along with molasses and Starbio significantly influenced the quality of rice straw following the fermentation. This suggests that the fermentation method can enhance the physical and chemical qualities of rice straw, thereby boosting its potential value as an animal feed component.